Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/ijms.61975
|View full text |Cite
|
Sign up to set email alerts
|

Thymopentin treatment of murine premature ovarian failure via attenuation of immune cell activity and promotion of the BMP4/Smad9 signalling pathway

Abstract: Premature ovarian failure (POF) is a typical form of pathological aging with complex pathogenesis and no effective treatment. Meanwhile, recent studies have reported that a high-fat and high-sugar (HFHS) diet adversely affects ovarian function and ovum quality. Here, we investigated the therapeutic effect of thymopentin (TP-5) as a treatment for murine POF derived from HFHS and its target. Pathological examination and hormone assays confirmed that TP-5 significantly improved murine POF symptoms. And, TP-5 coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(130 reference statements)
0
14
0
Order By: Relevance
“…Our past work demonstrated that POF was a result of pathological ovarian aging and it had very close contact with HFHS-induced oxidative stress [ 7 9 ]. Currently, EA is an effective strategy for the treatment of POF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our past work demonstrated that POF was a result of pathological ovarian aging and it had very close contact with HFHS-induced oxidative stress [ 7 9 ]. Currently, EA is an effective strategy for the treatment of POF.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research [ 22 , 23 ]. In addition, HFHS diet could induce oxidative stress in the female reproductive system [ 7 9 ]. Oxidative stress was defined as an imbalance between ROS production and the antioxidant capacity of cell [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid oxidative stress injury and polarization of immune cells are inhibited and the release of inflammatory factors is increased in POF mice. Zhu et al reported that the concentrations of IL-1 β , IL-6, IL-4, IL-22, NF- κ B, TNF- α and IFN- γ in the peripheral blood of POF mice were significantly decreased after thymopentin treatment [ 52 ]. Yin et al reported that Th17/Tc17 cells, Th17/Treg cells, or IL-17 expression were increased, restoring ovarian function after human placenta mesenchymal stem cells were transplanted into POF mice [ 53 ].…”
Section: Application Of Traditional Chinese Medicine In Pofmentioning
confidence: 99%